Anti-gout potential of traditional medicinal plants enriched with flavonoids: a systematic review - Fitri Suhaimi, Nurul Shahira; Begum, Taslima; Ali Shah, Syed Adnan; Helal Uddin, A.B.M.; Zakaria, Zainul Amiruddin; Ahmed, Qamar Uddin (MS-Editions (Chile), 2026)
The global prevalence of gout is increasing, with current pharmacological treatments often proving inadequate or causing adverse effects, especially in chronic cases. This has spurred interest in safer, natural alternatives. Flavonoids found in fruits, vegetables, and herbs exhibit antigout potential through xanthine oxidase (XO) inhibition, uric acid reduction, and anti-inflammatory effects. This review evaluates the pharmacological potential of flavonoid-rich traditional medicinal plants for gout treatment, analyzing in vivo, in vitro, and in silico studies from 2003 to 2023. Using the QuADS tool, 30 articles on 18 plant species were assessed. The findings reveal that flavonoids demonstrate significant antigout activity, particularly via XO inhibition and inflammation modulation. Promising in vivo results were observed in rodent models, despite variability in flavonoid concentration and formulation. Blumea balsamifera, Chrysanthemum sinense, Gnaphalium affine, Kaempferia parviflora, Perilla frutescens and luteolin stood out for their consistent efficacy. These insights support further research into flavonoids as natural agents for gout management.